2021
DOI: 10.3390/coatings11010091
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Coating and Wood Flooring Surface System Properties

Abstract: Parquet flooring is one of the most common types of flooring, the surface of which can be covered with various coatings. To avoid possible damage to the parquet during use, it is necessary to test the surfaces before installation according to various non-standard and standard protocols. The present study provides an overview of the interactions between the properties of selected waterborne coatings (solids content, hardness, resistance to cracking, tensile strength) and the properties of oak wood flooring surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…Even though oils enhanced the wood's natural appearance, they had limited resistance to chemicals [35]. In their study, Pavlic et al [34] showed that the resistance to cold liquids including coffee, ethanol, red wine, water, and paraffin oil, among others, depended on the properties of the topcoat. In terms of surface chemical resistance, no major differences were found [34].…”
Section: Evaluation Of the Coated Samples Resistance To Cold Liquidsmentioning
confidence: 99%
See 4 more Smart Citations
“…Even though oils enhanced the wood's natural appearance, they had limited resistance to chemicals [35]. In their study, Pavlic et al [34] showed that the resistance to cold liquids including coffee, ethanol, red wine, water, and paraffin oil, among others, depended on the properties of the topcoat. In terms of surface chemical resistance, no major differences were found [34].…”
Section: Evaluation Of the Coated Samples Resistance To Cold Liquidsmentioning
confidence: 99%
“…In their study, Pavlic et al [34] showed that the resistance to cold liquids including coffee, ethanol, red wine, water, and paraffin oil, among others, depended on the properties of the topcoat. In terms of surface chemical resistance, no major differences were found [34]. In previous work, Nejad et al [32] showed that household chemicals including vegetable oil, ketchup, and mustard increased the gloss of coated oil-heat-treated samples made of maple, beech, and hemlock.…”
Section: Evaluation Of the Coated Samples Resistance To Cold Liquidsmentioning
confidence: 99%
See 3 more Smart Citations